Backtesting the Lee-Carter and the Cairns-Blake-Dowd stochastic mortality models on Italian death rates - Carlo Maccheroni; Samuel Nocito (Risks, 2017)
This work proposes a backtesting analysis that compares the Lee-Carter and the Cairns-Blake-Dowd mortality models, employing Italian data. The mortality data come from the Italian National Statistics Institute (ISTAT) database and span the period 1975-2014, over which we computed back-projections evaluating the performances of the models compared with real data. We propose three different backtest approaches, evaluating the goodness of short-run forecast versus medium-length ones. We find that neither model was able to capture the improving shock on mortality observed for the male population on the analysed period. Moreover, the results suggest that CBD forecasts are reliable prevalently for ages above 75, and that LC forecasts are basically more accurate for this data.
Keywords: 330; lee-carter model; cairns-blake-dowd model; backtesting; mortality forecast